Analisis Yuridis Terhadap Perlindungan Korban Kekerasan Seksual Dalam Perspektif Hak Asasi Manusia - Aulia Ilmi Sosia (CV. SINAR HOWUHOWU, 2025)
This article examines legal protection for victims of sexual violence in Indonesia from a human rights perspective. The main focus of the study is to analyze the effectiveness of Law Number 12 of 2022 concerning the Crime of Sexual Violence (UU TPKS) in providing justice, recovery, and victim-centered protection. Using a normative juridical approach and literature study, this research finds that although the UU TPKS represents significant legal progress, its implementation still faces numerous challenges, such as limited understanding among law enforcement officers, weak recovery services, and a lack of inter-agency coordination. Moreover, patriarchal culture and social stigma remain major barriers to victims' access to justice. Therefore, integrating a human rights-based approach into legal policy, public education, and service systems is crucial to ensure that victim protection becomes more comprehensive, just, and humane.